Our stolen future : are we threatening our fertility, intelligence, and survival? : a scientific detective story - Colborn, Theo; Dumanoski, Dianne; Myers, John Peterson (New York : Dutton, 1996)
Argues that the focus on the carcinogenicity of chemicals has led to the ignoring of the adverse effects of chemicals on the embryo and fetus. Resultant problems include reduced fertility, altered behavior patterns, and decreased immunity.
Omens -- Hand-me-down poisons -- Chemical messengers -- Hormone havoc -- Fifty ways to lose your fertility -- To the ends of the earth -- A single hit -- Here, there, and everywhere -- Chronicle of loss -- Altered destinies -- Beyond cancer -- Defending ourselves -- Loomings -- Flying blind -- Appendix: The wingspread consensus statement.
Includes bibliographical references and index.
Keywords: Reproductive toxicology; Environmental health; Endocrine disrupting chemicals